2012
DOI: 10.2298/vsp101224012s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the morphometric parameters of the intercondylar notch on rupture of the anterior cruciate ligament

Abstract: Enhanced height of the intercondylar notch as well as lesser value of the notch shape index are associated with rupture of the ACL in males but not in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Stijak et al studied gender based variation of femoral notch width and concluded females have narrower notch than men. 10 However, Anderson et al, found no statistically significant difference of NWI between the sexes(11). Domzalski et al, observed NWI with respect to gender did not make a difference, for factor contributing to ACL injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Stijak et al studied gender based variation of femoral notch width and concluded females have narrower notch than men. 10 However, Anderson et al, found no statistically significant difference of NWI between the sexes(11). Domzalski et al, observed NWI with respect to gender did not make a difference, for factor contributing to ACL injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced height of the intercondylar notch and lesser value of the notch shape index were associated with rupture of the ACL in males but not in females (Stijak et al 2012). It has been recently concluded that type A femoral notch appears to be a risk factor for ACL injury, whereas a reduced notch index has no significant correlation to ACL injury (Al-Saeed et al 2013).…”
Section: Radiographic Assessment Of Bone Morphology Risk Factorsmentioning
confidence: 97%
“…Discriminant analysis showed that the notch width at the inlet could be a predictor of ACL injury (Simon et al 2010). Enhanced height of the intercondylar notch and lesser value of the notch shape index were associated with rupture of the ACL in males but not in females (Stijak et al 2012). It has been recently concluded that type A femoral notch appears to be a risk factor for ACL injury, whereas a reduced notch index has no significant correlation to ACL injury (Al-Saeed et al 2013).…”
Section: Morphologic and Functional Mri Assessment: Pktd ®mentioning
confidence: 99%